2020
DOI: 10.1101/2020.09.18.20186866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical characteristics of children with COVID-19 admitted in a tertiary referral center in Perú

Abstract: Introduction The COVID-19 pandemic has a great impact on children's health. This study describes the clinical, epidemiological and treatment characteristics of children presenting COVID-19 at the Instituto Nacional de Salud del Niño San Borja (INSN-SB) Methods This was a retrospective study of patients with a confirmed diagnosis of COVID-19 from March to July 2020. Demographic, clinical, laboratory, radiological, and treatment information were collected. Data analysis included descriptive statistics and bivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…7 In Italy, 5.9% (10/168) of study participants had co-infections, 16 while in Perú, M. pneumoniae was found in 10% (9/91) of participants. 53 In Latin America, 3.4% (14/409) of participants tested positive for a viral co-infection, although no significant association was found between co-infections and ICU admission or mechanical respiratory support. 22 In contrast, in Europe, 5% (29/582) of participants tested positive for a viral coinfection and patients with one or more viral co-infections were more likely to have signs or symptoms of upper or lower respiratory tract infection at presentation.…”
Section: Viral Co-infectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…7 In Italy, 5.9% (10/168) of study participants had co-infections, 16 while in Perú, M. pneumoniae was found in 10% (9/91) of participants. 53 In Latin America, 3.4% (14/409) of participants tested positive for a viral co-infection, although no significant association was found between co-infections and ICU admission or mechanical respiratory support. 22 In contrast, in Europe, 5% (29/582) of participants tested positive for a viral coinfection and patients with one or more viral co-infections were more likely to have signs or symptoms of upper or lower respiratory tract infection at presentation.…”
Section: Viral Co-infectionsmentioning
confidence: 99%
“…50 Older children were more likely to present with respiratory distress than infants (44% vs. 7%). 17 Less common symptoms include seizures 16,50,53 and loss of taste and smell. 4,17 A study of 2143 (731 laboratory-confirmed) pediatric cases reported to the Chinese Center for Disease Control and Prevention found that 94.1% of cases could be classified as asymptomatic, mild, or moderate.…”
Section: Clinical Presentation In Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical characteristics among COVID-19 pediatrics patients in different countries(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%